Adoption of M-Health Technologies: Economic Drivers of User Experience and Satisfaction in Consumer Decision-Making - Saputra, I Made Dwija Adi; Muna, Nilna (International Journal of Economics Development Research (IJEDR), 2025)
The development of m-Health technology in Indonesia faces significant challenges related to adoption and usage among the public. In this context, this study aims to analyze the influence of perceived ease of use on continuance usage intention, with user experience and satisfaction as mediating variables. The research method employed is a survey using a questionnaire distributed to 337 users of the Pramita Mobile application in several major cities. The analysis results using Partial Least Squares (PLS) indicate that perceived ease of use has a significant positive effect on user experience and satisfaction. Furthermore, both variables also contribute positively to continuity usage intention. This study finds that user experience and satisfaction function as mediators linking perceived ease of use with continuance usage intention. The conclusion emphasizes the importance of enhancing the ease of use of applications to improve user experience and satisfaction. Thus, strategies focusing on increasing usability will be beneficial for encouraging the adoption and continued use of m-Health applications in Indonesia, thereby providing greater health benefits to the community. This research offers valuable insights for application developers in creating more effective and user-friendly solutions